TERMINOLOGY AND FORM OF THE INCOME SHEET. - Bowers, Russell (The Accounting Review, 1944)
Abstract The article presents information on the general-purpose terminology and form which should contribute to the effectiveness of annual reports. The question, therefore, is not what income statements actually mean as they are now published, but what they can be made to signify. Consideration of the content of the report is here omitted so far as the important problem of valuation is concerned. The title "Profit and Loss" does not describe the nature of this report as it has been developed in recent years. The name does not suggest the very important accounting category of expense. Moreover, the report contains many elements other than losses. The term profit is somewhat antiquated in comparison with income as a general descriptive term. Profit is definite and meaningful only in the sense of transaction profit; but transaction profit is only a small part of what the report is designed to display. Some income, as well as many kinds of expense, is and must be apportioned as a function of time or other bases, and accordingly the result is not strictly profit based upon a completed transaction or a number of transactions.